Impact of pharmacist intervention on antibiotic use and prophylactic antibiotic use in urology clean operations. (25th April 2015) - Zhou, Y.; Ma, L.‐Y.; Zhao, X.; Tian, S.‐H.; Sun, L.‐Y.; Cui, Y.‐M.
Summary What is known and objective The use of prophylactic antibiotics in clean operations was routine in China before 2011. Along with the appeal for using antibiotics rationally by WHO in 2011, China launched a national special rectification scheme on clinical use of antibiotics from April that year. The scheme, aimed at achieving rational use of antibiotics, made pharmacists part of the responsible medical team. Our objective was to describe the impacts of pharmacist intervention on the use of antibiotics, particularly in urology clean operations. Methods Pharmacists participated in antibiotic stewardship programmes of the hospital and urological clinical work and conducted real‐time interventions at the same time from 2011 to 2013. Data on the use of antibiotics between 2010 and 2013 in urology were collected. Results Comparison of the 2013 data with those of 2010 showed that antibiotic use density [AUD= DDDs*100/(The number of patients who were treated the same period*Average days in hospital). DDDs = Total drug consumption (g)/DDD. DDD is the Defined Daily Dose] decreased by 57·8(58·8%); average antibiotic cost decreased by 246·94 dollars; the cost of antibiotics as a percentage of total drug cost decreased by 27·7%; the rate of use of antibiotics decreased from 100% to 7·3%. What is new and conclusion The study illustrates how an antibiotic stewardship programme with pharmacist participation including real‐time interventions can promote improved antibiotic‐prescribing and significantly decrease costs.